Economic Evaluation of Changes in Reimbursement for Medications Purchased Through the 340B Drug Pricing Program. (August 2021) - Endriukaitis, Lauren A.; Hayes, Genevieve L.; Mills, Jason
Background: The Centers for Medicare and Medicaid Services (CMS) implemented changes to the reimbursement scheme for 340B-acquired medications on January 1, 2018, reducing payments by approximately 25%. It was recognized that these changes would have a significant fiscal impact to Medical University of South Carolina (MUSC) Health. The purpose of this assessment was to review the financial impact of changes in Medicare reimbursement for clinic-administered medications.Methods: This study was a single-center, retrospective, financial evaluation of closed outpatient encounters for Medicare beneficiaries in calendar year 2018. Actual reimbursement was calculated for 2018. To better characterize the margin obtained, exploratory analyses were completed to identify best- and worst-case reimbursement outcomes. This exploratory analysis was conducted for both the new (ASP-22.5%) and old (ASP+6%) reimbursement schemes.Results: Overall, 10 973 encounters were reviewed for inclusion. Ultimately, 8028 encounters were included in the final analysis. Of all encounters, 88 unique medications were administered. Most of the drugs (55%) were associated with oncologic indications. An unfavorable variance was found in 3761 encounters (47%). The actual reimbursement margin for 2018 was $3 193 525.Conclusion: Changes to reimbursement outlined by the CMS at the start of 2018 resulted in decreased reimbursement for 340B-eligible, clinic-administered medications. Most of the unfavorable variances were associated with 340B acquisition prices that exceeded reimbursement. Although the original intent of the 340B Drug Pricing Program was to stretch federal resources, decreased payments could reduce institutional ability to fund programs that support medically vulnerable populations.